2022 American Society of Anesthesiologists Practice Guidelines for Management of the Difficult Airway - Apfelbaum, Jeffrey L; Hagberg, Carin A; Connis, Richard T; Abdelmalak, Basem B; Agarkar, Madhulika; Dutton, Richard P; Fiadjoe, John E; Greif, Robert; Klock, P Allan; Mercier, David; Myatra, Sheila N; O'Sullivan, Ellen P; et al. (Anesthesiology (Philadelphia), 2022)
The American Society of Anesthesiologists; All India Difficult Airway Association; European Airway Management Society; European Society of Anaesthesiology and Intensive Care; Italian Society of Anesthesiology, Analgesia, Resuscitation and Intensive Care; Learning, Teaching and Investigation Difficult Airway Group; Society for Airway Management; Society for Ambulatory Anesthesia; Society for Head and Neck Anesthesia; Society for Pediatric Anesthesia; Society of Critical Care Anesthesiologists; and the Trauma Anesthesiology Society present an updated report of the Practice Guidelines for Management of the Difficult Airway.